The Effect Of Corporate Values, Conservatism, And Earnings Quality On Audit Opinion Going Concern - Surjadi, Merna; Sofianty, Dianmonalisa; Whittleliang Hakki, Tandry; Pohan, Pricilla (DINASTI RESEARCH, 2024)
Financial Report is the final result of the accounting cycle which is a record of financial information used to describe the financial condition of the company as information for external and internal parties of the company. The purpose of the report is to provide information on the financial position, financial performance and cash flow of the entity that is useful for most users of the report in making economic decisions (Minerva et al., 2020). Earnings quality is often associated with the quality of financial statement audits. the high value of the company, the tendency not to do a going concern audit opinion is greater, because a good company value is considered the profit generated by the company is stable. So this will attract management's interest in practicing going concern audit opinions. This study aims to test two influences, namely the influence of Company Value and conservatism on the going concern audit opinion carried out by the company and the influence of Company Value and conservatism on Earnings Quality. This study took the research population from financial sector companies listed on the Indonesia Stock Exchange for the period 2019-2021. The type of data used in this study is secondary data in the form of financial reports of companies that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of this study, it shows that Firm Value and Earnings Quality has an effect on the Audit Opinion Going Concern, But Conservatism has not effect on Opinion Audit Going Concern. This explains that with the high value of the company, the tendency not to do a going concern audit opinion is greater, because a good company value is considered to be a stable profit generated by the company. So this will attract management's interest in practicing going concern audit opinions.